1997
DOI: 10.1007/bf02258399
|View full text |Cite
|
Sign up to set email alerts
|

Oral fleet® phospho®-soda laxative-induced hyperphosphatemia and hypocalcemic tetany in an adult

Abstract: Although Fleet Phospho-Soda solution continues to be a safe bowel preparation, caution should be used in adults with bowel obstruction and renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 9 publications
1
37
0
1
Order By: Relevance
“…Physiologic causes of hyperphosphatemia include decreased glomerular phosphate clearance due to renal failure, release of endogenous phosphate stores as in tumor lysis syndrome and rhabdomyolysis, and increased renal tubular reabsorption of phosphate as in hypoparathyroidism [10,11]. Administration of phosphate containing products, such as certain enemas and laxatives, has also resulted in symptomatic hyperphosphatemia [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Physiologic causes of hyperphosphatemia include decreased glomerular phosphate clearance due to renal failure, release of endogenous phosphate stores as in tumor lysis syndrome and rhabdomyolysis, and increased renal tubular reabsorption of phosphate as in hypoparathyroidism [10,11]. Administration of phosphate containing products, such as certain enemas and laxatives, has also resulted in symptomatic hyperphosphatemia [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and reports have demonstrated significant serum electrolyte disturbances associated with oral NaP administration including hyperphosphatemia and hypocalcemia [5][6][7][8][9][10][11]. In patients without comorbid conditions, these electrolyte changes are usually transient and clinically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da reconhecida eficácia, o NaP tem sido incriminado em decorrência dos efeitos colaterais indesejáveis 9,63 , mormente os distúrbios eletrolíticos e as lesões renais [64][65][66][67][68][69] motivos pelos quais há vários alertas, por iniciativa do FDA, nos últimos 5 anos 70 , ou por estudos que salientam sua ação deleté-ria mesmo quando se trata de rins normais 71,72 . Embora as soluções com sais de fosfato seja um atrativo por causa do pequeno volume a ser ingerido -seja na forma de solução ou de comprimidos -e haja considerações de segurança no que diz respeito ao risco de hiperfosfatemia, hipernatremia, hipocalemia ou de hipocalcemia, deve-se observar, com insistência, que esses efeitos têm potencial para causar desidratação, acidose metabólica, insuficiência renal, tetania ou mesmo morte 9,[73][74][75][76][77][78][79][80][81] , além do que, também há um descuido geral no que diz respeito aos riscos para os pacientes com doenças cardíacas, renais e hepáticas 82,83 . Por outro lado, o aumento progressivo da idade e a presença distúrbios da função renal são fatores de relevância para o alerta de problemas iminentes 84 .…”
Section: Fostato De Sódio (Nap)unclassified